New species, synonymy and records for New World Lamiinae (Coleoptera, Cerambycidae) - Bezark, Larry G.; Santos-Silva, Antonio (Zootaxa, 2022)
Two new species are described: Callia breviantennata (Calliini), from Peru; and Etyma maculata (Desmiphorini), from Mexico. Desmiphora (Desmiphora) ornata Bates, 1866 (Desmiphorini) is recorded from Argentina. Ataxia linearis (Bates, 1866) is synonymized with A. mucronata (Bates, 1866) (Pteropliini), and new records are provided. New country and state records are provided for two species of Eupogonius. An updated key to species of Callia, and a key to species of Etyma are provided.